2017
DOI: 10.1074/jbc.m116.774075
|View full text |Cite
|
Sign up to set email alerts
|

The sigma-1 receptor modulates dopamine transporter conformation and cocaine binding and may thereby potentiate cocaine self-administration in rats

Abstract: The dopamine transporter (DAT) regulates dopamine (DA) neurotransmission by recapturing DA into the presynaptic terminals and is a principal target of the psychostimulant cocaine. The sigma-1 receptor (σR) is a molecular chaperone, and its ligands have been shown to modulate DA neuronal signaling, although their effects on DAT activity are unclear. Here, we report that the prototypical σR agonist (+)-pentazocine potentiated the dose response of cocaine self-administration in rats, consistent with the effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
79
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(88 citation statements)
references
References 48 publications
9
79
0
Order By: Relevance
“…However, if α4 were to move to a greater degree, it could disrupt the oligomerization interface. This is consistent with prior data, which suggest that σ1 receptor agonists bias the receptor towards lower molecular weight states, while antagonists bias it towards higher molecular weight states 4,[22][23][24] . Additionally, molecular modeling by Yano et al predicted that (+)-pentazocine and other multimer-impeding ligands would occupy this space differentially from haloperidol and other multimer-promoting ligands 24 , which is consistent with our structural results.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…However, if α4 were to move to a greater degree, it could disrupt the oligomerization interface. This is consistent with prior data, which suggest that σ1 receptor agonists bias the receptor towards lower molecular weight states, while antagonists bias it towards higher molecular weight states 4,[22][23][24] . Additionally, molecular modeling by Yano et al predicted that (+)-pentazocine and other multimer-impeding ligands would occupy this space differentially from haloperidol and other multimer-promoting ligands 24 , which is consistent with our structural results.…”
Section: Discussionsupporting
confidence: 92%
“…While there are myriad proposed binding partners for the σ1 receptor 1,3,4,19,30 , the critical effectors of σ1 receptor signaling still need to be unambiguously established. Future work will need to focus on these functional questions in order to fully understand the function of the σ1 receptor and its potential as a therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patch-clamp and amperometry in cells and in vivo chronoamperometry revealed a s 1 Rmediated decrease in methamphetamine-stimulated DA efflux. Another study (Hong et al, 2017) showed that the s 1 R agonists (1)-pentazocine and PRE-084 increased the B max values of [ 3 H] WIN35,428 in radioligand binding assays both in cultured cells and rat striatal synaptosomes. Further, coimmunoprecipitation and bioluminescence resonance energy-transfer assays indicated an interaction between s 1 R and DAT in transfected cells.…”
Section: Tablementioning
confidence: 98%